Academic Resistance in the University: Conceptualizing the Phenomenon. Issue 1 (2nd January 2018) - Korbut, A.M.
Abstract : This article analyzes the phenomenon and concept of "academic resistance." Several aspects are identified: resistance as an integral part of power relations in university education, the pragmatic nature of resistance, and the impossibility of constructing an overarching conception of resistance. The author concludes that researching particular cases of academic resistance is important to developing a deeper and more integrative understanding about the identities of various actors that are part of university educational practices.